2008
DOI: 10.1590/s0101-81752008000400008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest heterogeneity on occurrence and abundance of the scale-backed antbird, Hylophylax poecilinotus (Aves: Thamnophilidae), in the Amazon forest

Abstract: Recently, a significant number of studies on neotropical forest bird communities have focused on factors influencing their richness, abundance, and habitat selection. However, few of them have considered populations or individual species, and how habitat structure affects their distribution and abundance. In this study, we investigated how the combined effects of some forest structure components affect the occurrence and abundance of a resident bird species, the scale-backed antbird Hylophylax poecilinotus (Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…If true that many life history strategies predispose some species to be negatively impacted by the road, some species may actually benefit (Coffin, 2007). Ecological studies on road impacts need to be focused on target groups such as understory insectivores, which require specialized habitat requirements, large areas, the existence of a continuous matrix of vegetation, and the availability of primary forests and specific food resources (Cintra & Cancelli, 2008;Lees & Peres, 2008;Stratford & Stouffer, 2013;Sánchez et al, 2014). Since many of these species are difficult to detect, the implementation of different sampling techniques (i.e., mistnets, translocation studies, and radio-tracking) could help to complement point count censuses (Develey & Stouffer, 2001;Laurance, 2004;Laurance & Gomez, 2005).…”
Section: Does the Highway Affect The Abundance And Distribution Of Unmentioning
confidence: 99%
See 1 more Smart Citation
“…If true that many life history strategies predispose some species to be negatively impacted by the road, some species may actually benefit (Coffin, 2007). Ecological studies on road impacts need to be focused on target groups such as understory insectivores, which require specialized habitat requirements, large areas, the existence of a continuous matrix of vegetation, and the availability of primary forests and specific food resources (Cintra & Cancelli, 2008;Lees & Peres, 2008;Stratford & Stouffer, 2013;Sánchez et al, 2014). Since many of these species are difficult to detect, the implementation of different sampling techniques (i.e., mistnets, translocation studies, and radio-tracking) could help to complement point count censuses (Develey & Stouffer, 2001;Laurance, 2004;Laurance & Gomez, 2005).…”
Section: Does the Highway Affect The Abundance And Distribution Of Unmentioning
confidence: 99%
“…The quality of the territory varies with arthropod abundance (i.e., availability of aerial litter) and the complexity of forest structure (Cintra & Cancelli, 2008) influencing the distribution and density of these species (Laurance, 2004), some of which could survive fragmentation as long as small corridors connect forest patches (i.e., Sánchez et al, 2014). We noticed that some species (i.e., White-breasted Wood Wren, H. leucosticta, and the Spectacled Antpitta, Hylopezus perspicillatus) maintained well-established territories and were found predictably at specific points along the trails.…”
Section: Does the Highway Affect The Abundance And Distribution Of Unmentioning
confidence: 99%
“…Whether these habitat features (forest structure components and local terrain ruggedness) are considered to be crucial components of birds' niches (PIANKA 1974, WIENS et al 1987) needs further investigation. Nevertheless, other bird species abundance and changes in bird community compositions in relation to changes in the forest structure in Central Amazon forest has also been recently documented (see below, andCANCELLI 2008, BANKS &CINTRA 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Some components of habitat structure or floristic composition may determine availability of food, nesting sites, or refuge from predators, and habitat features are considered to be crucial components of birds' niches (PIANKA 1974, WIENS et al 1987. Although the effects of habitat heterogeneity on bird populations and communities have received far more attention in temperate regions than in the tropics (REY 1995 but see CINTRA et al 2006, CINTRA & CANCELLI 2008, BANKS-LEITE & CINTRA 2008, understanding how the structure of tropical forests vary is important to describe the bird assemblages associated to them, and to identify the mechanisms that allow high species coexistence. Tropical forests, however, are a complex environment and detecting exactly what components of the vegetation affect bird distribution and abundance is not trivial.…”
mentioning
confidence: 99%
“…Birds may be attracted to gaps due to the presence of more 'edge' habitats; more foliage at net level, which can be used for protection against predators; increased availability of perches; and higher primary productivity of these sites (Schemske and Brokaw 1981). In fact, Willis (1982) and Cintra and Cancelli (2008) reported that the distribution of this species occurs mainly in open canopy and in sites with leaf litter.…”
Section: Discussionmentioning
confidence: 99%